Bathing beach, Trinidad, B.W.I. - (:unkn) unknown (Unknown, 2011)
A view of Macqueripe Bay located on the northern coastline of Chaguaramas, Trinidad.
Colour: Sepia; Style: Portrait; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Inlets--Trinidad and Tobago; Beaches--Trinidad and Tobago; Beachgoers--Trinidad and Tobago